Rhetoric As A Discursive Strategy In Creating Skilled Saudi Graduates: A Case Study Of Prince Sattam Abdulaziz University - Naeem Afzal, Mohammed Ilyas, (Opción, 2019)
This research study assessed the extent to which rhetoric is included in textbooks and the curricula of skills courses and advanced courses of the undergraduate program in English Language and Literature at Prince Sattam Abdulaziz University (PSAU) via a content analysis with a case-based qualitative approach. The findings hinted at significant curricular connections between the study of rhetoric in skills courses and of the advanced level courses. In conclusion, the study recommends designing a separate course track or a module on Rhetoric and align it with the other closely related courses at all levels.